1994
DOI: 10.1523/jneurosci.14-10-05917.1994
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sprouting of filopodia in nerve terminals of chromaffin cells, PC12 cells, and dorsal root neurons induced by electrical stimulation

Abstract: Rapid morphological changes induced by direct electrical stimulation of nerve terminals were studied by using video-enhanced differential interference contrast microscopy at a very high magnification (12,000x). We used mainly cultured bovine chromaffin cells, which developed neurite-like processes, and PC12 cells, which showed neuronal differentiation upon NGF treatment. In a few cases, primary neurons of the rat dorsal root ganglion were also examined. Brief pulse stimulation of the terminals and varicosities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…In PC12 cells stimulation has been observed to lead to rapid sprouting of filopodia (Manivannan and Terakawa, 1994). This activity-dependent growth of filopodia is F-actin and myosin II dependent and leads to an increase in chromaffin and PC12 cell footprint size (Fig.…”
Section: F-actin Dependent Plasma Membrane Morphology Changes Followimentioning
confidence: 94%
“…In PC12 cells stimulation has been observed to lead to rapid sprouting of filopodia (Manivannan and Terakawa, 1994). This activity-dependent growth of filopodia is F-actin and myosin II dependent and leads to an increase in chromaffin and PC12 cell footprint size (Fig.…”
Section: F-actin Dependent Plasma Membrane Morphology Changes Followimentioning
confidence: 94%
“…In particular, G i , G o and G q/11 transduce hormone and neurotransmitter receptormediated modulation of ion channels 4,11,23,40) . In neurons, transmembrane Ca ‫ם2‬ entry via voltage-dependent calcium channels (VDCCs) is of major physiological importance, because several neuronal functions such as neuronal excitability 29) , neuronal migration 28) , neurite outgrowth 25,30,34) , gene expression, and neurotransmitter release, depend on this event.…”
Section: Introductionmentioning
confidence: 99%
“…ES of nerve terminals has been shown to induce rapid filopodial sprouting in primary neuron cell cultures in the presence of extracellular Ca 2+ [3]. It has also been reported that, following sciatic nerve crush injury in rats, administering ES accelerates the appearance of the toespreading reflex, a sensitive indicator of the onset of motor recovery [8], further supporting the concept that ES enhances early regeneration events that initiate sprout formation.…”
Section: Discussionmentioning
confidence: 77%
“…Our initial studies investigated the therapeutic potential of ES in nerve regeneration following a rat facial nerve crush injury because of ES's enhancing effects on the morphological and functional properties of neurons [1][2][3][4]. In these studies, daily, low-frequency ES hastened the onset of recovery of the eye blink reflex by reducing the initial delay in sprout formation rather than by increasing the rate of axonal regeneration, indicating that ES acts primarily on events in the early stages of recovery [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation